2021
DOI: 10.1002/jcp.30499
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin‐A excess expression  amplifies lipid induced apoptosis and β‐cell damage

Abstract: Fetuin-A, a hepato-adipokine, is associated with lipid-mediated islet inflammation and inflicts β-cell death but the underlying mechanisms are still unclear. In an earlier report, it was shown that fetuin-A promotes lipid-induced insulin resistance by acting as an endogenous ligand of toll like receptor 4. Recently, we have also reported that β-cells secrete fetuin-A on stimulation by palmitate causing β-cell dysfunction. The aim of this study was twofold: (a) screening the role of fetuin-A in survival of muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…On the other hand, fetuin-A levels have been shown to be significantly lower in the setting of ischemic cardiomyopathy, as compared with that of dilated cardiomyopathy, potentially providing fetuin-A with a discriminative power between these different types of HF. 88 Results of different studies regarding fetuin-A confirm its contribution to the pathogenesis of IR; it seemingly impedes the maturation of β cells in the pancreatic islets, 89 enhances apoptosis and damages pancreatic β cells when oversecreted, 90 and is overexpressed at the initiation of a high-fat diet, concurrent with IR, in murine models. 91 Additionally, fetuin-A along with a Western lifestyle are held accountable for the development of IR, vascular inflammation and atherosclerosis, 92 as well as for the development of T2D in people of Pakistani origin.…”
Section: Insulin Resistancementioning
confidence: 91%
“…On the other hand, fetuin-A levels have been shown to be significantly lower in the setting of ischemic cardiomyopathy, as compared with that of dilated cardiomyopathy, potentially providing fetuin-A with a discriminative power between these different types of HF. 88 Results of different studies regarding fetuin-A confirm its contribution to the pathogenesis of IR; it seemingly impedes the maturation of β cells in the pancreatic islets, 89 enhances apoptosis and damages pancreatic β cells when oversecreted, 90 and is overexpressed at the initiation of a high-fat diet, concurrent with IR, in murine models. 91 Additionally, fetuin-A along with a Western lifestyle are held accountable for the development of IR, vascular inflammation and atherosclerosis, 92 as well as for the development of T2D in people of Pakistani origin.…”
Section: Insulin Resistancementioning
confidence: 91%
“…It is an endogenous inhibitor of the insulin-stimulated insulin receptor tyrosine kinase, and insulin resistance substrate-1. Elevated Fetuin A levels in pancreatic beta cells increase macrophagesmigration and cause beta cell in ammation (12).Experimental studies have suggested critical role of circulatory fetuin-A and β-cell secreted fetuin-A in β-cell dysfunction and apoptosis (13). Clinical studies have shown it to be an independent risk factor for T2D (14).…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic β-cells treated with fetuin-A and FFA (palmitate) have been associated with beta cell failure and apoptosis, which is suggested to be mediated through the TLR4-signaling pathway (Shen et al, 2015). Consistently, a follow-up study by Mukhuty et al (2022) unveiled that fetuin-A plays a critical role in triggering FFA-mediated beta cell inflammation, beta-cell dysfunction, and apoptosis by inducing lipotoxicity and activating the TLR4-NF-κB pathway in hyperlipidemic conditions. More interestingly, the apoptosisinducing activity of fetuin-A has also been observed in cancer cell lines, such as mouse P388 leukemia and PC-3 prostate cancer models, with no effect on normal cell lines, suggesting its potential use as a selective anticancer agent.…”
Section: Inflammatory and Anti-inflammatory Roles Of Fetuin-amentioning
confidence: 93%
“…Fetuin-A also aggravates IR by inducing fetuin-A secretion from pancreatic beta cells, which promotes macrophages migration and transformation into the M1 phenotype in islets, elicits beta cell inflammation, and impairs their function. ( Agarwal et al, 2017 ; Mukhuty et al, 2017 ; Mukhuty et al, 2021a ; Mukhuty et al, 2022 ). This fetuin-A-mediated chronic beta cell inflammation occurs in hyperlipidemic conditions and is linked with beta cell apoptosis, mass reduction, and dysfunction, leading to decreased insulin secretion and worsening of IR ( Hennige et al, 2008 ; Shen et al, 2015 ).…”
Section: Biological Roles Of Fetuin-amentioning
confidence: 99%